Listeria monocytogenes Infection in Hairy Cell Leukemia: A Case Report and Literature Review - James C. Barton; Hayward S. Edmunds (Case Reports in Hematology)
Listeria monocytogenes infections have been described in patients with diverse types of malignancy, especially leukemia. We report the case of a 65-year-old man with previously untreated hairy cell leukemia characterized by CD5 positivity and trisomy 12 (3% of blood lymphocytes) who developed bacteremia due to L. monocytogenes serotype 1/2b. We summarize clinical features and treatment of this patient and five previously reported patients with hairy cell leukemia who also had L. monocytogenes infections. All six patients were men. Their mean age at infection diagnosis was 70 y. Three men had undergone splenectomy 4–11 y before they developed L. monocytogenes infection. The central nervous system was the primary site of infection in four men. Bacteremia alone occurred in two other men. At diagnosis of infection, one man was receiving antileukemia chemotherapy and another man was receiving treatment for Kaposi’s sarcoma. Two other patients had other comorbid conditions. All six men recovered from their infections.